Acid shock protein Asr induces protein aggregation to promote E. coli O157:H7 entering viable but non-culturable state under high pressure carbon dioxide stress. (February 2023) - Pan, Hanxu; Yang, Dong; Wang, Yongtao; Rao, Lei; Liao, Xiaojun
Abstract: Under stressful conditions, bacteria can enter viable but non-culturable (VBNC) state to survive. VBNC cells lost ability to grow on routine culture medium but are still alive and may revive in suitable conditions. The revived cells can consume nutrients or produce toxins, leading to food spoilage or human illness, posing great risk to food safety and public health. Previously, we have reported that high pressure carbon dioxide (HPCD), an environment-friendly sterilization technology, can induce VBNC formation. However, the underlying mechanism is unclear. By performing a comprehensive transcriptomic analysis, we revealed that HPCD initiated high expression of asr, encoding an acid shock protein, could promote VBNC formation of E. coli O157:H7. Quantitative reverse transcription PCR analysis suggested that high expression of asr (i) inhibited acid resistance (AR) systems, resulting in endogenous proton accumulation; (ii) inhibited hchA expression, a protein stabilizing factor. The two effects resulted in endogenous protein aggregation, which was highly correlated to VBNC formation. Accordingly, HPCD-stressed cells exhibited decreased efficiency of electron transfer chain and ATP production, which was also contributory to cytoplasmic protein aggregation. Taken together, HPCD-initiated high expression of Asr coupled with decreased ATP production led to protein aggregation, finally promoted the cells to enter VBNC state. Highlights: Molecular responses of E. coli O157:H7 to HPCD were investigated to explore crucial factors regulating VBNC formation. Acid shock protein Asr was found to be involved in regulating HPCD induced VBNC formation. Asr inhibited AR systems / protein stabilizer HchA to facilitate endogenous protein aggregation to promote VBNC formation.